Willingness and Perceived Barriers towards Organ Donation among Student Nurses in Universiti Malaysia Sabah - R. Segaran; Mohd Amsyar bin Bacho; Asrani Yaco (2018)
Organ transplant has become a main stream important medical procedure commonly used in hospitals. However, for organ transplant program to be successful, it heavily relies on the public to voluntarily register for organ procurement. Effort to promote awareness and register public as organ donors has been ongoing, but public response to commit and register as donors has been lukewarm. Arguably, healthcare personnel and nurses are in a key position to educate and advocate for organ donation but often, ironically healthcare personal themselves are reluctant or unwilling to commit as organ donors. Thus, in the context of student nurses in University Malaysia Sabah, the question arise, what is their stance and views regarding organ donation? Objective: The study aims to explore student nurses willingness and perceived barriers towards organ donation. Method: By design, this is a quantitative and descriptive cross-sectional study. Sampling, involved a convenient cohort of all 169 diploma nursing students currently studying in year 1, 2 and 3 in UMS. The study instrument used included a self-rated question adopted from a previous study to assess the willingness and perceived barriers towards organ donation. Findings: Among 169 respondents, only 5.9 % (n=10) were registered organ donors. Among perceived barriers included i) fear of medical side effects or disability (85.7% n=145), ii) religious taboo and beliefs (71.5 % , n=121), iii) family reluctance (65.6% , n=111) iv) and distrust of organ procurement process (51% n=87). Conclusion: There is a gap in commitment towards organ donation associated with a number of perceived barriers among student nurses in UMS. The paper will discuss some pragmatic strategies to address this gap.